Design of IoT Enabled Three Phase Power Quality Monitoring Unit Based on EmonLibCM Library - Prasetyo, Hoedi; Sugiarto, Yohanes; Raharja, Agung Budi; Rachmawan, Anggara Oksean; Mahadi, Benidektus Datu; Pratama, Febriansyah Putra (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2024)
This research presents the development of a cost-effective and reliable three-phase power quality monitoring device using readily available components and the open-source EmonLibCM library. The device addresses the limitations of existing single-phase devices, offering comprehensive monitoring for industrial applications with capacities above 100 kVA. The system architecture utilizes multiple Arduino boards for sensor data processing and a Raspberry Pi for data communication, storage, and user interface. Node-RED facilitates real-time data visualization on a user-friendly dashboard, while SQLite enables data logging for further analysis. The device accurately measures essential electrical parameters, including voltage, current, real power, apparent power, frequency, and energy consumption, with an average error of less than 5% compared to a reference Power Quality Analyzer. This research contributes to the advancement of affordable and accessible power quality monitoring solutions, promoting better energy management practices in industrial settings.